Readiness of Indonesian pre-service science teachers for society 5.0 - Irwandani, Irwandani; Suyatna, Agus; Haenilah, Een Yayah; Maulina, Dina (Intelektual Pustaka Media Utama, 2024)
This research aimed to assess the readiness of Indonesian pre-service science teachers by examining their perceptions of impending challenges, desired competencies, and anticipated instructional methodologies in preparing for the challenges of Society 5.0. Using a quantitative survey research methodology, 884 pre-service science teachers from 16 universities were surveyed. The research instrument's validity and reliability were assessed utilizing the Rasch model. Inferential statistics were employed to assess the readiness of pre-service science teachers for future challenges, taking into account their backgrounds. The test outcomes showed the Cronbach's Alpha coefficient reached 0.92, is deemed